Pottery and cultural interaction from 3000 to 600 BP Batanes, Northern Philippines - De Leon, Alexandra S (2008)
This study examines the nature of prehistoric cultural interaction in the Batanes between 3000-600 BP, as evidenced by pottery assemblages excavated from the Savidug Dune Site on Sabtang and Anaro on Itbayat. The study defines the nature of prehistoric pottery assemblages from Savidug Dune Site and Anaro in terms of vessel shape, surface finish/decoration and compositional attributes. The study also compares the assemblages and establishes that similarities and variation in pottery forms and decoration occur from 3000 to 600 BP and determines that around 3000-2700 BP, there was greater similarity in vessel from and decoration in both sites. At 1000-600 BP, continuing but still diminished contact occurred between the inhabitants of Sabtang and Itbayat. Thin-section analysis indicates that pots were not exchanged between Savidug and Anaro but rather produced locally on each island. Similarity in form and decoration of pottery assemblages therefore is explained by cultural interaction between occupants of archaeological sites from 3000-600 BP.